Effect of Variations in Pyrolysis Reactor With Glass Wool Equipped and Without Glass Wool on the Weight of the Oil Produced - Santhiarsa, IGN Nitya (Journal of Mechanical Engineering Science and Technology (JMEST), 2021)
Currently, plastic waste is a very serious threat because plastic waste pollution can harm all living things around and also harm the environment. The increasing volume of plastic waste is due to the lack of processing technology, so that the volume of plastic waste is increasing day by day. Plastic is a material that is difficult to decompose because it is non-biodegradable. One application of plastic waste processing technology offered in this study is to use the pyrolysis principle. Pyrolysis is a method of converting plastic into fuel oil through a thermal decomposition process without the use of oxygen. The pyrolysis process used with a variety of reactors equipped with glass wool and reactor variations without glass wool. The purpose of this study was to compare the yield of pyrolysis oil with a variety of reactors equipped with glass wool and reactors without glass wool. The plastic used is OPP (oriented polypropylene), with a constant reactor heating temperature of 200° C. The pyrolysis process is carried out for 1 hour each test, and the condenser cooling temperature is 28° C. Based on the results of the research, the reactor variation with glass wool got the highest oil weight of 175 grf, while the reactor variation without glass wool got the lowest oil weight of 17 grf. With a variety of reactors equipped with glass wool, the heat generated is more concentrated into the reactor core, resulting in higher oil weight and a more efficient pyrolysis process.